2019
DOI: 10.1016/j.afjem.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nurse-led tranexamic acid administration protocol for trauma patients in rural South Africa

Abstract: Introduction Administration of tranexamic acid (TXA) has been shown to effectively reduce all-cause mortality in trauma patients when given within three hours of injury. We found that many trauma patients in our hospital were not receiving TXA. This was due to a variety of factors, including late presentation to hospital, lack of staff awareness, short staffing, and unavailable drugs or equipment. Our aim was to develop a protocol for safe, nurse-led administration of TXA in the emergency centre i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Recent studies have shown the potential benefits of APN in emergency care in Africa. For example, a study conducted in South Africa found that implementing a nurse‐led trauma service was associated with improved patient outcomes, including reduced mortality rates and shorter hospital stays; however, the enhanced outcomes might be seen as a result of both system‐ and nursing‐related contributions, illustrating the importance of integrating nursing expertise within the trauma care system to improve patient outcomes (Christmals & Armstrong, 2019a, 2019b; Wearmouth & Smith, 2019). Similarly, a study conducted in Nigeria found that utilizing APNs in emergency care was associated with improved triage and patient outcomes (Chimezie & Ibe, 2019).…”
Section: Sources Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the potential benefits of APN in emergency care in Africa. For example, a study conducted in South Africa found that implementing a nurse‐led trauma service was associated with improved patient outcomes, including reduced mortality rates and shorter hospital stays; however, the enhanced outcomes might be seen as a result of both system‐ and nursing‐related contributions, illustrating the importance of integrating nursing expertise within the trauma care system to improve patient outcomes (Christmals & Armstrong, 2019a, 2019b; Wearmouth & Smith, 2019). Similarly, a study conducted in Nigeria found that utilizing APNs in emergency care was associated with improved triage and patient outcomes (Chimezie & Ibe, 2019).…”
Section: Sources Of Evidencementioning
confidence: 99%
“…The intervention involved training APN to provide trauma care and lead the trauma team. The study found that implementing the trauma service was associated with improved patient outcomes, including reduced mortality rates and shorter hospital stays (Wearmouth & Smith, 2019). This was similarly done in Uganda, where nurses were trained to provide care to trauma patients, and this showed a reduction in fatality rates compared with other rates in regions (Chamberlain et al., 2015).…”
Section: Sources Of Evidencementioning
confidence: 99%
“…Regarding emergency centre trauma care, Wearmouth and Smith report on their clinical governance project in a rural South African district hospital in KwaZulu-Natal, where they aimed to improve the administration of tranexamic acid to pertinent trauma admissions using a nurse-led protocol, since the delays to administration were identified in a prior audit at their facility. [9] They report a good experience and low protocol deviation rate and postulate that this intervention may reduce mortality in rural trauma cases.…”
mentioning
confidence: 98%